Question #37a30

1 Answer
Aug 19, 2016

Answer:

See below.

Explanation:

Let us assume that the reaction is under the following general form:

#A+B->C#

The rate law is determined experimentally to be:

#R=k[A][B]^2#

The rate law with the first concentrations could be written as:

#R=k[A_1][B_1]^2#

If the concentration of #A# is doubled, this means that the new concentration is: #[A_2]=2xx[A_1]#

and the concentration of #B# is tripled: #[B_2]=3xx[B_1]#

Replacing the new concentration in the expression of the rate law: #R'=k[A_2][B_2]^2#

Therefore, we have:
#R'=k[A_2][B_2]^2=k(2xx[A_1])(3xx[B_1])^2#

#=>R'=(2)(3)^2xxunderbrace(k[A_1][B_1]^2)_R#

#=>R'=(2)(3)^2xxR#

#=>R'=2xx9xxR#

#=>R'=18xxR#

Which indicates that the rate of the reaction will increase by a factor of #18#.

Here is a complete lesson on reaction rate:
Chemical Kinetics | Reaction Rates & Rate Law.